CHALLENGES AND OPPORTUNITIES FOR THE APPLICATION OF AI IN LANGUAGE LEARNING IN INDONESIA - Syarifudin, Albitar Septian (Transpublika Publisher, 2023)
Advances in artificial intelligence (AI) technology have had a significant impact across various sectors, including language education. In Indonesia, the implementation of AI in language learning presents substantial opportunities, such as personalized learning and innovative assessment methods. However, there are significant challenges, including infrastructure limitations, technology access gaps, and a lack of teacher training. This research aims to analyze the challenges and opportunities of implementing AI in language learning in Indonesia. The study uses a descriptive qualitative method that combines in-depth interviews with education practitioners, language teachers, and technology experts, as well as document analysis from related literature. The results show that while AI can enhance the quality of learning through adaptive and interactive experiences, its implementation is still hindered by uneven infrastructure, especially in remote areas, and the need for more inclusive language processing models. In conclusion, collaboration among the government, educational institutions, and technology developers is crucial to addressing these challenges and maximizing the potential of AI in language education in Indonesia.